Developing low temperature recovery technology of waste heat in automobile factory. Issue 5 (23rd August 2018) - Chang, Dong‐Shang; Cheng, Kun‐Ping; Wang, Rouwen
Abstract: The painting operation is an important process in automobile manufacturing process, which not only consumes considerable amount of energy but also affects the environment through the flue gases emitted during the process. A case study in Taiwan was conducted on developing an innovative low‐temperature recovery technology of waste heat automobile industry. The high frequency welding segment technology was built on the site to extract heat close to an acid dew point. When the ambient temperature is changed substantially, the fins and heat pipes are solidly connected to maintain the performance of the heat exchanger. Moreover, the hot water obtained from the waste heat recovery is delivered to pretreatment heating tank the painting shop directly. By improving the energy efficiency on heat transfer, the proposed recovery technology of waste heat in automobile factory has been justified with having the performance 69% higher than conventional design. In order to reduce the effect of CO2 emission on the environmental impact, the temperature at the end of the flue gases is further decreased from 160° C to 110° C. The cost benefit analysis reveals that the payback year is 2.8 years. The innovative heat recovery technology contributes to energy conservation and environmental sustainability. Abstract : By improving the energy efficiency on heat transfer, the proposed recovery technology of waste heat in automobile factory has been justified with having the performance 69% higher than conventional design. High‐frequency welding technology used in low‐temperature waste heat recovery can be extended to other industries such as hot water boilers. The innovative heat recovery technology contributes to energy conservation and environmental sustainability.